O tempo da greve: o caso da comunidade quilombola Pitoró dos Pretos. - ANDRADE NETO, João Augusto de (2009)
This work consists basically in a case study made with the families from Pitoró dos Pretos, a community that defines itself as a comunidade remanescente de quilombos, from the municipality of Peritoró, at the region called Médio Mearim of Maranhão estate. We tried to develop the social dynamics that configured a faccional disruption inside the group. The official actions executed by agents of the official establishment in land reform processes and quilombolas territorial regularization are taken as object of analysis and questioned in their fundaments. We identified several social agents and social organizations whom established alliances with the members of Pitoró dos Pretos all along a process of land conflict in the nineteen s. Utilizing oral memory methods of research, we reconstructed the land struggle history which Pitoró dos Pretos families lived, known as o tempo da greve. The workers were annually submitted to the payment of a rent price for the owner of the land, by offering part of the food genres produced by their families. After a year characterized by the lack of rain, they have lost their agriculture production and could not pay it. This was the turning point where from started a movement with the participation of a lot of families from three different villages named Pitoró, Resfriado e Precateira, united by the objective of getting rid with the economical and political subordination to the land owner. Based upon this case study we intend to put in evidence the fact that communities whom members are self-defined as quilombolas are characterized by an ethnical identity that lies bellow the public assumption as comunidades remanescentes de quilombos, which is utilized for interlocutions with external agents and Nation-State officers. They are not an innovation provided by the institution of the 68 article from the ADCT part of the Brazilian Federal Constitution. The case of Pitoró dos Pretos is a demonstration of this proposition: the land struggle process lived by the group happened before the existence of the constitutional article. We understand that is figures as a situation similar as so many others found not just at Maranhão state, but also in other places of the national territory. Their common trace is a continued territorial resistance, despite of the marginal position occupied by this groups inside the juridical establishment and even against it.